2005
DOI: 10.1103/physrevlett.95.193903
|View full text |Cite
|
Sign up to set email alerts
|

Complete Band Gaps in One-Dimensional Left-Handed Periodic Structures

Abstract: Artificially fabricated structures with periodically modulated parameters such as photonic crystals offer novel ways of controlling the flow of light due to the existence of a range of forbidden frequencies associated with a photonic bandgap. It is believed that modulation of the refractive index in all three spatial dimensions is required to open a complete bandgap and prevent the propagation of electromagnetic waves in all directions. Here we reveal that, in a sharp contrast to what was known before and cont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(55 citation statements)
references
References 16 publications
1
54
0
Order By: Relevance
“…We emphasize that the omnidirectional refl ectivity does not necessarily imply a complete PBG, since the latter is more strict, requiring that no mode can exist for any k || values including the cases of k || > ω / c . Shadrivov et al studied the problem in detail [73] . By thoroughly examining the Bloch equations for two polarizations [i.e., Eq.…”
Section: Complete Band Gapsmentioning
confidence: 99%
“…We emphasize that the omnidirectional refl ectivity does not necessarily imply a complete PBG, since the latter is more strict, requiring that no mode can exist for any k || values including the cases of k || > ω / c . Shadrivov et al studied the problem in detail [73] . By thoroughly examining the Bloch equations for two polarizations [i.e., Eq.…”
Section: Complete Band Gapsmentioning
confidence: 99%
“…The dispersion relations, reflection characteristics, group velocities and n eff of the periodic structure contain negative index materials is calculated numerically using transfer matrix method [16,19,26]. The geometry of the structure under study is shown in Fig.…”
Section: Theorymentioning
confidence: 99%
“…The complete band gap in one-dimensional left handed periodic structures has been purposed. The modulation of refractive index in all three spatial directions is required to find a complete band gap and prevent the propagation of electromagnetic waves in all directions [19][20][21]. Singh et al [22] have investigated the structural parameters for the formation of omni-directional band gaps in one dimensional photonic crystal.…”
Section: Introductionmentioning
confidence: 99%
“…One-dimensional photonic crystal consisting of alternate LHM and conventional right-handed material (RHM) layers have already been investigated through calculating the transmittance or the reflectance the structures (7; 15)and demonstrating of complete band gap (16). In this letter we demonstrate another example of unusual properties of LHM and study electromagnetic surface TE waves guided by an interface between RHM and a 1D periodic structure consisting of alternate LHM and RHM layers which we refer to lefthanded photonic crystal.…”
Section: Introductionmentioning
confidence: 99%